Influence of cathode polarization on protective properties of thermoreactive coatings for main pipelines - A. O. Rybakov, S. L. Melnychuk, S. O. Osadchuk, L. I. Nyrkova (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
The effect of cathodic polarization under cyclical temperature changing (from room temperature to 70 oC) on the protective properties of new and artificially aged heat-curing coatings for main pipelines has been investigated. It is shown that cathodic disbondment of coatings depends on their properties, temperature, applied potential. It has been established that the reducing (by absolute value) of the protective potential (with the IR component) from -1.45 to -0.75 V facilitate to retaining of the protective properties of coatings: the disbondment radius of a new hybrid-epoxide coating decreases in 3.3 times, aged coating – in 1.7 times, new and aged polyurethane coating – more than 20 times.